Genetic and genomic resources of Mithun – An update - Chotso, Kuluve; Harshit Kumar; Periasamy , Kathiravan; Patil, S. Girish (Journal of Livestock Biodiversity, 2025)
Mithun (Bos frontalis) is a unique bovine species native to the tropical rainforest regions of Northeast India and neighboring countries. This paper reviews the genetic and genomic resources of Mithun, highlighting its morphological diversity across distinct strains such as Arunachali, Nagami, Manipuri and Mizo Mithun. Each strain exhibits unique characteristics shaped by selective breeding and adaptation to varying environments. Recent genomic studies have provided insights into the genetic makeup of Mithun, revealing significant diversity and evolutionary connections with other bovine species, particularly the Gaur (Bos gaurus). However, Mithun populations face severe threats, including habitat fragmentation, inbreeding and increasing commercialization, which adversely affect their genetic health and ecological roles. Conservation efforts, including cryopreservation and artificial insemination, show promise for maintaining genetic diversity. The paper emphasizes the need for comprehensive strategies that integrate genomic research with sustainable breeding practices and habitat conservation. Collaborative efforts among government, researchers and local communities are essential to ensure the long-term viability of Mithun populations, preserving their cultural and ecological significance in the region.